“WALI SONGO” PERINTIS PENDIDIKAN ISLAM DI INDONESIA(Masa Awal Perkembangan Islam di Jawa) - Asgar Marzuki; Bahaking Rama; Mukjizah Mukhtar Lutfi (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Da'i is a symbol of proclaiming and carrying Islamic teachings, sincerely and selflessly for the efforts of li'ilai Kalimatillah (to elevate the word of Allah). Moving around the world with wealth and self without asking for wages, as a manifestation of the verses of the Koran, Q.S. as-Shaff/61:11 "You believe in Allah and His Messenger and strive in the way of Allah with your wealth and your soul, it is better for you if you know". It is proof that sincerity in the struggle is maintained when holding fast to this verse, as a limitation and rule in spreading dinul haq. To add insight into the perspective which states that Islam was brought by Gujarat traders and as proof that they are Da'i illallah (not traders) who bring their wealth and themselves in the struggle, do not beg and ask for payment, then when their supplies run out, they sell the treasures they brought as supplies with the barter trading system, at that time was the easiest and most common way to do it, because cross-border currency exchange instruments had not yet been implemented. "Wali Songo" is a title that has been assigned to nine Preachers who have been pioneers of Islamic education in Indonesia. The historicity of the growth and development of Islamic education, especially on the island of Java, is marked by the existence of Islamic educational institutions initiated by "Wali Songo" and given the name pesantren, as the center of Islamic educational activity. In all its manifestations, pesantren with the characteristics attached to these institutions, have varied forms with the characteristics, patterns and nuances of each wisdom. Islamic education has a substantial and functional relationship, namely it has become a vehicle for ongoing Islamic educational activities since its inception, which functions as an instrument for the inculcation of Islamic beliefs and doctrines. The growth of pesantren institutions as Islamic educational institutions in Java has taken place gradually, starting from the very simple pesantren model to the highest level which in its development has contributed to the civilization of life and has even overseen all forms of change and development in Bhinneka Tunggal Ika, with various pluralism, cultures , culture and language of the unitary state of the Republic of Indonesia which respect each other in diversity and glorify in civilization. "Wali Songo" has succeeded in responding with wisdom to diversity, present politely and peacefully without engaging in conflict and violence, writing a golden ink history of love and Islamic peace, as teachings, sharia and guidance to the essence of happiness Rahmatan lil 'Aalamiin